SIRT6, oxidative stress, and aging - Liao, Chen-Yu (Cell Res, 2016)
The role of oxidative stress in the aging process has been highly debated for decades and remains equivocal. A new study published in Cell Research reports a novel role for the aging-associated SIRT6 deacetylase in the control of oxidative homeostasis in human mesenchymal stem cells.